KEPEMIMPINAN KEPALA MADRASAH DALAM MENGEMBANGKAN KOMPETENSI PROFESIONAL GURU NON-LINEAR DI MADRASAH TSANAWIYAH SWASTA MA’UNAH SARI KECAMATAN PAMENANG KABUPATEN MERANGIN JAMBI - Rizka Arianti; Rusmini; Abdullah Yunus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by the high number of non-linear teachers at MTs S Ma’unah Sari, Pamenang District, Merangin Regency, Jambi, where 5 out of 10 teachers teach subjects that do not match their educational background. This condition is not supported by specific coaching programs from the principal, resulting in suboptimal development of non-linear teachers’ professional competence. The purpose of this study is to analyze the role of the principal’s leadership, the efforts undertaken, and the challenges faced in improving the professional competence of non-linear teachers. This research employs a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The data sources consist of the principal, the vice principal, and non-linear teachers. Data were analyzed using Miles and Huberman’s model, which includes data reduction, data display, and conclusion drawing, with data validity ensured through triangulation of sources, techniques, and time. The findings indicate that the principal’s leadership has not provided targeted, needs-based coaching for non-linear teachers. The efforts made are limited to giving motivation, directing teachers to join MGMP (subject teacher forums), and utilizing general workshops that are not specifically designed for non-linear teaching challenges. Teachers largely improve their competence independently through self-learning and consulting senior teachers. Major challenges include limited subject mastery, weak IT skills, minimal learning facilities, and budget constraints. In conclusion, the professional development of non-linear teachers is strongly influenced by the effectiveness of the principal’s leadership. More structured, intensive, and needs-oriented coaching is required to ensure non-linear teachers can teach professionally.